Knowledge management: An analysis of knowledge storage amongst consultant firms in Malaysian construction industry - Othman, Azlan; Ismail, Syuhaida; Yahya, Khairulzan (Journal of Management, Economics, and Industrial Organization, 2018)
In recent years, a major challenge in the field of knowledge management (KM) has been the way in which KM is implemented. Individuals and organisations are starting to understand and appreciate knowledge as the key element in the emerging competitive environment. As a preparation for the competitive industrial nation, KM is an important countenance that should be the point of convergence for the industry players. This paper wishes to draw the attention on the important of KM storing practice by focusing on consultant firms in construction industry in Malaysia. Questionnaires were distributed to about 200 respondents working in the industry, with the aim of investigating the KM storage implementation in the Malaysian consultant firms. In this paper, the data is analysed using Statistical Package of Social Sciences (SPSS) version 23.0. The analysed results from questionnaire survey and focus group showed that consultant firm in construction industries were involved in implementing KM storing in their organisation. This paper is beneficial in order to improve the KM storing practice in the organisation.
Keywords: Knowledge management; consultant firm; civil engineering; Malaysian construction industry; KM Storing; KM implementation